Viscoelastic flows of cholesteric liquid crystals - Orlandini, E; Marenduzzo, D; Yeomans, J (2007)
We numerically solve the hydrodynamic equations of motion for a cholesteric liquid crystal under an imposed Poiseuille flow, by means of lattice Boltzmann simulations. The elasticity of the cholesteric helix couples to the external flow to give rise to a highly viscoelastic flow. This is a technically difficult problem for standard flow solvers due to its fully two-dimensional nature. We consider a helix with axis parallel to the boundaries, and at the same time to either the primary flow or the vorticity direction (we identify these two flow modes as permeation and vorticity mode respectively). We quantify the large difference found in the steady state director and velocity profiles, and in the apparent viscosities obtained in the two cases.